Implementing Project-Based Learning: the Experience of a Military Medical Educational Organization - T. B. Sviridova; A. S. Lutikov; E. A. Goldina; N. N. Kamynina; Yu. V. Burkovskaya (Здоровье мегаполиса)
Introduction. The implementation of project-based learning into programs of advanced professional education is one of the most relevant areas of development in the modern education system. Project-based learning significantly increases the efficiency of the educational process and the interest of students in the subjects studied and contributes to the development of their leadership qualities. The acquired skills can be successfully applied to professional activities.The article examines the successful implementation of project-based learning using the example of a military medical educational organization and determines positive aspects that can be used in other education sectors.The purpose of the study was to identify the advantages and disadvantages of project-based learning in comparison to traditional forms of education.Materials and methods. In the study, methods of sociological research were used. Students engaged in traditional and project-based learning were asked to fill out questionnaires. Then, a comparative content analysis was performed. Statistical processing and analysis of the data obtained were carried out.Results and discussion. The study of students' satisfaction with traditional and project-based learning showed that the second group had better motivation, higher interest in the subject, and a higher level of academic performance. The average academic performance score in the project-based groups was 4.8, while in the group of traditional education it was only 4.2. Conclusion. The implementation of project-based learning in academic departments is aimed at increasing students’ professional competencies, acquiring and improving additional professional skills, and creating and implementing innovative schemes that can be used later in a medical organization as independent projects. Project-based learning is more effective than traditional learning in terms of critical thinking, communication and organizational skills, and teamwork experience. The practice of analytical, strategic, and planning skills as a team is an important skill difficult to acquire in traditional training.